Posdaya Sebagai Alternatif Pemerataan Pendidikan Anak Usia Dini - Murfi, Ali; Jannah, Rina Roudhotul (Al-Athfal: Jurnal Pendidikan Anak, 2017)
This research is intended to reveal the importance of Posdaya as an alternative in equal distribution of early childhood education which is the community-based organization or educational embodiment of, by and for the community. The results showed that the implementation of the model of Posdaya is one of alternative in the equal distribution of early childhood educational levels or it which is called PAUD. The organization of PAUD Posdaya is evidence of the the answers of credibility the challenge of demographic bonus the year 2045, or 100 years of independence of Indonesia and can be a solution related to a classical problem of educational about equal distribution that occurred in Indonesia. Some of the things that make Posdaya important to be held because the first, Posdaya get higher percentage of community pasticipation. The second, it can be reached by all circles of society, especially medium to bottom class people. The third is as media to synergize the existence of each instituiton in society, such as government programs related to toddler, mothers, and society as Posyandu, PKK, BKB, KB, the national program for community empowerment (PNPM Mandiri), and other empowerment programs.